Clinical course of a fetus with hypoplastic left heart syndrome and premature ductal constriction. (27th December 2018) - Krishnan, Anita; Tague, Lauren; Rudra, Harish; Pradhan, Subechhya; Vezina, Gilbert; Limperopoulos, Catherine
Abstract: Premature ductal constriction was diagnosed in a 30-week gestation fetus with hypoplastic left heart syndrome. The fetus developed right ventricular hypertrophy and mild tricuspid regurgitation. Foetal neuroimaging showed slowed growth of the brain and increased lactate. We describe the imaging and clinical findings. Fetuses with critical CHD and in utero ductal constriction are at increased risk of morbidity and mortality, and require appropriate counselling.